The Effect of the Couple Card–Based Make a Match Learning Model on Elementary School Students' Creativity in Mathematics Learning - Sudarsono Sudarsono; Nursofiana Safitri; Sumiyati Sumiyati; Hasan Hasan (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2026)
This study examined whether students' creativity scores differed before and after the implementation of the Couple Card-based Make a Match learning model in elementary mathematics learning. A quantitative pre-experimental one-group pretest-posttest design was used with 25 fifth-grade students as participants. Creativity data were collected using a mathematics creativity test administered before and after the treatment and were analyzed using descriptive statistics, normalized gain (N-Gain), normality testing, and paired-samples t-test with IBM SPSS. The results showed that the mean creativity score increased from 64.20 in the pretest to 81.40 in the posttest. The N-Gain score was 0.48, indicating a moderate improvement. The paired-samples t-test showed a significant difference between pretest and posttest scores (t = 6.412; df = 24; p < 0.05), with a large effect size (Cohen's dz = 1.28). These findings indicate that the Couple Card-based Make a Match learning model is associated with improved students' creativity in elementary mathematics learning. However, because this study used a one-group pretest-posttest design without a control group, the findings should be interpreted proportionally.